From basic to clinical translation: advances and perspectives of photodynamic nanodrugs - Ma, Shitang; Shi, Shasha; Hu, Xin; Zhao, Ye; Yang, Boran; Liao, Maoliang; Lu, Baowei; Xu, Qilin (Frontiers in Pharmacology, 2025)
Photodynamic nanodrugs (PDNS) have demonstrated significant advantages in enhancing therapeutic outcomes while reducing systemic toxicity, achieved primarily through optimized photosensitizer solubility, targeted biodistribution, and site-specific accumulation. This review systematically examines recent progress and future directions of PDNS development, encompassing fundamental research to clinical translation. Specifically, it analyzes the composition, mechanisms of action, inherent advantages, clinical applications, as well as the challenges faced in this domain. The introduction of nanocarriers has circumvented the limitations of the core photosensitizers, substantially enhancing the efficacy and safety of PDNS via targeted delivery and synergistic therapy. Moreover, the integration of stimuli-responsive and multifunctional nanoplatforms has further improved the spatiotemporal control of reactive oxygen species (ROS) generation, thereby minimizing off-target effects. In addition, the combination of PDNS with immunotherapy has exhibited synergistic effects, underscoring the potential of this integrated approach. PDNS has made remarkable progress in cancer treatment through receptor-mediated endocytosis, self-assembly, and precise targeting. Beyond cancer treatment, PDNS holds considerable promise in treating a diverse array of non-oncological diseases, such as acne, psoriasis, dry eye disease, and cardiovascular disorders, et al. In this regard, PDNS has emerged as a pivotal component within the realm of personalized medicine. Despite these notable advancements, challenges persist in optimizing drug delivery and achieving efficient clinical translation. Looking ahead, future perspectives encompass the development of highly efficient photosensitizers and ensuring accurate nanocarrier delivery, which will undoubtedly facilitate the progress of PDNS in the clinical application field.